2015
DOI: 10.3892/etm.2015.2274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamins E and C combined with β-carotene on cognitive function in the elderly

Abstract: The aim of the present study was to investigate the effect of vitamins E (VE) and C (VC), combined with β-carotene (β-C), on cognitive function in the elderly. A total of 276 elderly subjects completed the prospective study following treatment with VE, VC and different doses of β-C or with VE only. Cognitive function was assessed by the Mini-Mental State Examination (MMSE) and Hasegawa Dementia Scale (HDS) tests. The plasma levels of amyloid-β (Aβ) and estradiol (E2) were determined by radioimmunoassay (RIA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…On the other hand, a randomized control trial involving 276 elderly participants demonstrated that 16-week-co-supplementation of vitamin E and C with β-carotene significantly improved cognitive function (particularly with higher doses of β-carotene). Furthermore, the authors suggested that such a treatment markedly reduced plasma Aβ levels and elevated plasma estradiol levels [ 80 ]. Vit C and E co-supplementation for more than 3 years was also shown to be associated with a reduced prevalence and incidence of AD [ 81 ].…”
Section: Role Of Vitamin C In Neurodegenerative Diseasesmentioning
confidence: 99%
“…On the other hand, a randomized control trial involving 276 elderly participants demonstrated that 16-week-co-supplementation of vitamin E and C with β-carotene significantly improved cognitive function (particularly with higher doses of β-carotene). Furthermore, the authors suggested that such a treatment markedly reduced plasma Aβ levels and elevated plasma estradiol levels [ 80 ]. Vit C and E co-supplementation for more than 3 years was also shown to be associated with a reduced prevalence and incidence of AD [ 81 ].…”
Section: Role Of Vitamin C In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Some of the most important carotenoids in terms of biotechnological and biomedical uses explored so far are: Astaxanthin (3,3′-dihydroxy-β,β′-carotene-4,4′-dione) [ 36 , 39 , 40 ], β-Carotene (β,β-carotene) [ 38 , 41 , 42 , 43 , 44 ], Canthaxanthin (β,β-carotene-4,4′-dione) [ 45 , 46 , 47 , 48 ], β-Cryptoxanthin (hydroxy-β-carotene) [ 38 , 49 , 50 , 51 , 52 , 53 , 54 ], Fucoxanthin [ 38 , 55 ], Lycopene (ψ,ψ-carotene) [ 33 , 56 , 57 ], Lutein (β,ε-carotene-3,3′-diol) [ 42 , 58 , 59 , 60 , 61 ], Zeaxanthin (β,β-carotene-3,3′-diol) [ 38 , 62 , 63 ], and Violaxanthin (5,6:5′,6′-diepoxy-5,5′,6,6′-tetrahydro-β-carotene-3,3′-diol) [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Carotenoids: Structure and Functionalitymentioning
confidence: 99%
“…However, there was only borderline or little evidence of a cognitive benefit from use of antioxidant supplements, particularly vitamins C and E, according to at least six independent cohort studies [ 54 , 60 , 84 , 85 , 86 , 87 ], and several cross-sectional studies [ 61 , 84 ]. Nevertheless, at least a few randomized controlled trials (RCTs) have indicated a benefit from supplementation with vitamin C [ 88 ], particularly among non-smokers [ 89 ], or from a combination of various antioxidants (including vitamins C, E, and β-carotene) [ 90 , 91 ], while other RCTs that focused on vitamin E supplementation failed to do so [ 92 , 93 , 94 ]. In our study, adjustment for supplemental intake of antioxidants did not alter the key findings with dietary antioxidants as the main exposures.…”
Section: Discussionmentioning
confidence: 99%